New opportunities in sustainable stormwater management in Hungary - Almási, Balázs (4D Journal of Landscape Architecture and Garden Art, 2007)
Last year in Hungary new perspectives were opened by the building regulation changes in the field of urban planning. New approach was declared in the subject of stormwater management in the new Building Art. The draft of Building Regulation of Budapest in turn after a leng while specifies the construction of public open spaces in new development areas. At the same time new expectations were rolled up by the people of Budapest, about the quality of the environment and the quality of public open spaces. In this background a complex and sustainable planning process is needed in stormwater management and open space design. The planning of sustainable stormwater facilities can not be done by drainage engineers alone. For a successful result it is necessary to actively involve all different departments of the city (urban planning, park & recreation, environment, drainage etc.), at an early stage in the planning process. This topic is introduced through some Western European examples.